2020
DOI: 10.1111/1471-0528.16412
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on reported outcomes and outcome measures in female idiopathic chronic pelvic pain for the development of a core outcome set

Abstract: Background A core outcome set (COS) is required to address inconsistencies in outcome reporting in chronic pelvic pain (CPP) trials. Objectives Evaluation of reported outcomes and selected outcome measures in CPP trials by producing a comprehensive inventory to inform a COS. Search strategy Systematic review of randomised controlled trials (RCTs) identified from Cochrane Central Register of Controlled Trials (CENTRAL), Embase and MEDLINE databases. Selection criteria RCTs assessing efficacy and safety of medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 24 publications
1
34
0
1
Order By: Relevance
“…The detrimental impact of CPP on quality of life outcomes has been described and identified as a priority for women with CPP [18]. Despite this, quality of life assessment is only reported by half of RCTs evaluating treatments for CPP [5]. Our findings demonstrated that all guidelines referred to the measurement of quality of life; however, there was no recommendation regarding which measurement instrument to utilize.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The detrimental impact of CPP on quality of life outcomes has been described and identified as a priority for women with CPP [18]. Despite this, quality of life assessment is only reported by half of RCTs evaluating treatments for CPP [5]. Our findings demonstrated that all guidelines referred to the measurement of quality of life; however, there was no recommendation regarding which measurement instrument to utilize.…”
Section: Discussionmentioning
confidence: 69%
“…The shortage of primary research supporting the management of women with CPP may prohibit the development of useful guidelines [18]. Furthermore, the quality of existing RCTs evaluating CPP interventions is variable with significant variability in outcome selection and reporting [5]. A working group within CHORUS is currently in the progress of establishing core outcome sets (COS) in CPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pertinent issues related to management of conditions may be overlooked and not reflective of patient priorities. For example, a systematic review of reported outcomes in therapeutic interventions in CPP demonstrated that quality of life was only reported by half of trials [23]. However, our study indicated that poor quality of life was a prevalent and reoccurring theme for women suffering with CPP.…”
Section: Discussionmentioning
confidence: 58%
“…Dyspnoea/shortness of breath/ been reported in areas such as delirium, hearing loss, chronic pelvic pain, and breast reconstruction, with studies concluding the need for consensus on outcomes and their associated measures for use in future clinical trials in these disease areas. [19][20][21][22] To our knowledge, this is the first study to examine how SARS-CoV-2 infection outcomes are measured in registered COVID-19 prevention trials. However, there are some methodological limitations.…”
Section: Discussionmentioning
confidence: 99%